SZ_GERICHTE ZK2 2017 97 vom 8. Oktober 2018 , dauernde Bodenverschiebung (Art. 660a ZGB) (EGV-SZ 2018 A 2.3) - SZ Gerichte (2018)
dauernde Bodenverschiebung (Art. 660a ZGB) (EGV-SZ 2018 A 2.3) | Justizverwaltung Zivilsachen/Grundbuch